Fight Alzheimer's with vitamins and antioxidants - Prasad, Kedar N. frey50 (Rochester, Vermont Healing Arts Press, 2015)
"The most complete and up-to-date resource on the powerful benefits of nutritional supplements for the treatment and prevention of Alzheimer's disease [bullet] Provides an easy-to-follow program of supplements to optimize the benefits of Alzheimer's treatment and maximize the impact of prevention strategies [bullet] Shows how standard treatments do not counteract the oxidative stress and chronic inflammation at the source of Alzheimer's [bullet] Also addresses related complications and symptoms such as altered sleep patterns, memory impairment, and behavior changes like depression and anger In this practical scientific guide, leading researcher in cancer, heart disease, and diabetes prevention Kedar N. Prasad, Ph.D., reveals the latest revolutionary discoveries on the use of antioxidants to prevent and treat Alzheimer's disease. He details how the proper combinations of vitamin and antioxidant supplements can greatly increase the effectiveness of standard medical treatments for Alzheimer's as well as delay or even prevent onset despite a family history of the disease. Prasad shows how oxidative stress and chronic inflammation play a significant role in the initiation and progression of neurodegenerative diseases like Alzheimer's. He provides an easy-to-follow daily supplement regime for multiple age groups to target free radical damage and inflammation and stop the progression of Alzheimer's and related complications such as altered sleep patterns, memory impairment, and behavior changes like depression and anger. Reviewing the scientific research on supplements and Alzheimer's, he debunks the flawed conclusions of the neurological community that vitamins and antioxidants are ineffective, revealing how their studies focused on specific micronutrients used alone rather than synergistic combinations. Offering the missing complement to the standard care of medications promoted by mainstream medicine, this guide provides a truly holistic approach to Alzheimer's prevention, treatment, and care"--
"The most complete and up-to-date resource on the powerful benefits of nutritional supplements for the treatment and prevention of Alzheimer's disease" --
Includes bibliographical references and index
Keywords: Alzheimer's disease -- Treatment; Vitamin therapy; Antioxidants -- Therapeutic use; Health & Fitness / Diseases / Alzheimer's & Dementia; Health & Fitness / Vitamins; Health & Fitness / Holism